2014
DOI: 10.1093/jisesa/ieu134
|View full text |Cite
|
Sign up to set email alerts
|

Infection With the Secondary Tsetse-Endosymbiont Sodalis glossinidius (Enterobacteriales: Enterobacteriaceae) Influences Parasitism in Glossina pallidipes (Diptera: Glossinidae)

Abstract: The establishment of infection with three Trypanosoma spp (Gruby) (Kinetoplastida: Trypanosomatidae), specifically Trypanosoma brucei brucei (Plimmer and Bradford), T. b. rhodesiense (Stephen and Fatham) and T. congolense (Broden) was evaluated in Glossina pallidipes (Austen) (Diptera: Glossinidae) that either harbored or were uninfected by the endosymbiont Sodalis glossinidius (Dale and Maudlin) (Enterobacteriales: Enterobacteriaceae). Temporal variation of co-infection with T. b. rhodesiense and S. glossinid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
5
13
0
Order By: Relevance
“…Our finding that higher proportions of tsetse flies infected with the endosymbiont S. glossinidus were infected with trypanosomes than those without S. glossinidius corroborates previous studies that suggest that S. glossinidius infection may have the potential to increase the ability of both wild caught [40,41] and lab reared [42,75] tsetse flies to acquire trypanosomes. Further, this finding implies that S. glossinidius infection in tsetse populations may be used as a positive indicator of trypanosomiasis risk.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that higher proportions of tsetse flies infected with the endosymbiont S. glossinidus were infected with trypanosomes than those without S. glossinidius corroborates previous studies that suggest that S. glossinidius infection may have the potential to increase the ability of both wild caught [40,41] and lab reared [42,75] tsetse flies to acquire trypanosomes. Further, this finding implies that S. glossinidius infection in tsetse populations may be used as a positive indicator of trypanosomiasis risk.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings revealed that humans, hippopotamus, and African buffaloes were the most frequent blood-meal sources of tsetse flies in the MMNR. We also found that the endosymbiont, S. glossinidius , was positively correlated with trypanosome infection in wild-caught G. pallidipes tsetse flies in the MMNR, supporting the hypothesis that Sodalis potentiates AAT transmission in tsetse flies [4042]. However, we found no correlation between Wolbachia and trypanosome infections, and no evidence of SGHV endosymbionts in the tsetse populations analyzed.…”
Section: Discussionsupporting
confidence: 81%
“…Other experimental studies revealed that the correlation between S. glossinidius and the ability of trypanosome to infect tsetse flies is trypanosome species-specific. For example, Wamwiri et al [ 25 ] demonstrated that teneral male G. pallidipes were about 6 times more likely to become infected by T. b. rhodesiense if they were infected with S. glossinidius while infection by T. b. brucei was not correlated with the presence of the endosymbiont. Wamwiri et al [ 25 ] also showed that T. congolense infection was 1.3 times more likely in flies not showing the presence of S. glossinidius .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it will also be critical to ensure that the recombinant Sodalis strain is transmitted from mother to offspring with a nearly 100% probability, and that it imposes only minor fecundity or mortality penalties. There is evidence that unmodified Sodalis alone may affect the fecundity or mortality of some tsetse species [ 14 , 26 , 27 ]. Of particular importance is the engineering of recombinant Sodalis to produce a molecule that effectively targets trypanosomes without simultaneously reducing the fitness of Sodalis .…”
Section: Discussionmentioning
confidence: 99%